Usability Testing on ITTS MART Prototype - Rizqa Amelia Zunaidi; Adek Dhea Resmi Purbantari; Fidelia Adinda Syafani; Hawwin Mardhiana; Ahmad Ihsan Fuady (Sistemasi: Jurnal Sistem Informasi, 2023)
Information technology is currently growing very rapidly so that it can provide convenience to its users, one of which is the ease of accessing the internet, such as through cell phones. The rapid increase in internet users, especially through mobile phones, is caused by the hectic number of social media applications as virtual friendship applications. Apart from being a virtual friendship application, another benefit of social media is as a promotional media, one of which is the promotion of online shopping applications, so that the number of online shopping transactions in Indonesia also increases. Hydroponic and aquaponic activities at the Telkom Institute of Technology Surabaya are also developing and starting to enter the product harvest stage, so a platform is needed to sell these products. An online shopping platform was chosen, especially a mobile application, to sell ITTelkom Surabaya products so that consumers can shop anytime and anywhere. The online shopping application developed by ITtelkom Surabaya is called ITTS MART. Currently, ITTS MART is still in the prototype development stage and there is a need for usability testing using the WebQual Concept on the ITTS MART application. From the results of the study, it can be concluded that the six research variables, namely Trust, Informational Fit-To-Task, Web Appearance, Entertainment, Government Policy and Transaction Capability, show a significant difference between expectations and real experience or dissatisfaction when using the ITTS MART application. Only one variable that shows the value of the difference is not significant, namely Response Time, so it can be concluded that respondents are satisfied with the time to access the page on the ITTS MART application.Keywords: Usability, WebQual, Online Shopping, Application, Food Product.